2009
DOI: 10.1111/j.1601-1546.2012.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behavior of radicular and coronal dentin

Abstract: Fracture of root‐filled teeth is not uncommon and appears to be a complex function of both the treatment and the patient's oral regimen. However, there have been few studies aimed at understanding the intrinsic mechanical behavior of dentin and its relevance to the incidence of these fractures. In addition, there has been some controversy over whether the fracture of root‐filled teeth is attributed primarily to loss of tooth structure or if there are other contributing factors. A comprehensive understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 110 publications
(203 reference statements)
1
46
0
2
Order By: Relevance
“…According to FE simulation, old apical dentine presented a maximum von Mises stress 3.9% higher than that of young dentine, which have been due to old dentine having a relatively higher elastic modulus than young dentine. Compared with young apical dentine, old apical dentine, with the higher stress level and the age-related reduction in the strength of root dentine, 31 could have a higher likelihood of damage occurrence. 32 Moreover, although a study on the effects of ageing on the fracture of apical dentine has not been conducted, it is expected that there would be a significant reduction in fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to FE simulation, old apical dentine presented a maximum von Mises stress 3.9% higher than that of young dentine, which have been due to old dentine having a relatively higher elastic modulus than young dentine. Compared with young apical dentine, old apical dentine, with the higher stress level and the age-related reduction in the strength of root dentine, 31 could have a higher likelihood of damage occurrence. 32 Moreover, although a study on the effects of ageing on the fracture of apical dentine has not been conducted, it is expected that there would be a significant reduction in fracture toughness.…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, although a study on the effects of ageing on the fracture of apical dentine has not been conducted, it is expected that there would be a significant reduction in fracture toughness. 31 Thus, due to a high stress level, a possible low strength and an expected low fracture toughness, old roots may become more susceptible to fractures than young roots.…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the significance of fracture to the field of dentistry, many investigations have been conducted to characterize the fracture properties of dentin. Reviews on this topic have been presented earlier [107,108].…”
Section: Fracture Properties Of Dentinmentioning
confidence: 99%
“…Results from that study distinguished that dentin is sensitive to flaws and that the methods presently used for cutting and removing demineralized tissues introduce detrimental defects. Of related importance, a recent preliminary study of dentin obtained from restored teeth, i.e., that underwent a period of oral function after placement of the restoration, showed substantially lower fatigue strength than unrestored tissue [107]. As dentin is not capable of repairing damage through a process of remodeling, the development of tools for minimizing the introduction of damage or the repair damage through remineralization processes are important considerations.…”
Section: Fatigue Properties Of Dentinmentioning
confidence: 99%
“…When a sufficient number of tubules have been filled, dentin appears transparent and this change is referred to as sclerotic dentin. 24 Thomas et al 25 have reported that sclerotic dentin is more prominent in teeth which have undergone endodontic treatment independent of the patients' age. It has been reported that dentin becomes more brittle with age.…”
Section: Age and Vrfmentioning
confidence: 99%